Cochrane Database of Systematic Reviews 2010
DOI: 10.1002/14651858.cd004714.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of periodontal disease for glycaemic control in people with diabetes

Abstract: There is some evidence of improvement in metabolic control in people with diabetes, after treating periodontal disease. There are few studies available and individually these lacked the power to detect a significant effect. Most of the participants in the study had poorly controlled Type 2 DM with little data from randomised trials on the effects on people with Type 1 DM.Improving periodontal health is an important objective in itself. However, in order to understand the potential of this treatment to improve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(58 citation statements)
references
References 79 publications
1
56
1
Order By: Relevance
“…There is evidence of a bidirectional relationship between diabetes and periodontal disease. 50,51 Oral fungal infections have also been associated with diabetes. 52 Hence, identifying patients with diabetes or prediabetes could help oral health professionals to better treat their patients.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence of a bidirectional relationship between diabetes and periodontal disease. 50,51 Oral fungal infections have also been associated with diabetes. 52 Hence, identifying patients with diabetes or prediabetes could help oral health professionals to better treat their patients.…”
Section: Discussionmentioning
confidence: 99%
“…Several recent systematic reviews (Teeuw et al, 2010, Simpson et al, 2010) have been conducted to assess the evidence that periodontal treatment influences glycaemic control. The aim of this manuscript is to provide an update to account for recent findings.…”
Section: Rationalementioning
confidence: 99%
“…A survey conducted in the United Kingdom found that 43% of adults reported avoiding the dentist due to cost. Of those adults, 26% reported suffering long-term tooth decay, and 13% reported suffering a periodontal abscess as a result (Simpson et al, 2010). A national sample of Canadian adults demonstrated that 30% reported avoiding or delaying dental visits, and 32.2% reported not being able to receive all the treatment that was recommended due to cost (Locker et al, 2011).…”
Section: Financial Barriers To Dental Carementioning
confidence: 99%
“…However, in most OECD settings dental care is largely separate. This is an important issue, particularly in ageing societies, since evidence is emerging that oral and systemic health are linked, particularly among populations with high chronic disease burdens (Lockhart et al, 2012;Simpson et al, 2010).…”
Section: Financial Barriers To Dental Carementioning
confidence: 99%
See 1 more Smart Citation